Locally Recurrent Leiomyoma of the Bladder Refractory to Visually Complete Transurethral Resection: An Indication for Cystoprostatectomy. (25th August 2019) - Mitchell, Katharina; Barnard, John; Luchey, Adam
Abstract : Leiomyomas are benign smooth muscle tumors that have low malignant potential (0.1%) and can arise in nearly any area of the body. Genitourinary involvement is very rare and represents only 0.05% of all bladder tumors (Mendes et al., 2017; GÖK, 2017). The most common presenting symptoms of bladder leiomyomas are obstructive voiding (49%), irritative voiding (38%), and hematuria (11%) (Goluboff et al., 1994). Treatment involves complete excision, in this case transurethral resection (TUR), and generally results in complete cure with no recurrences noted in the 250 cases reported in the literature for open resection and 18% recurrence rates after TUR which were successfully treated with a repeat TUR in all cases. Herein, we report a case of leiomyoma of the bladder which was refractory to four visually complete transurethral resections and ultimately required radical cystoprostatectomy with ileal conduit urinary diversion.